Closure of oroantral fistula. - Awang, M.N. (Elsevier, 1988)
Oroantral fistula is an uncommon complication in oral surgery. Although smaller fistulas of less than 5 mm in diameter may close spontaneously, larger fistulas always require surgical closures. The literature review revealed various procedures for the closure of oroantral fistulas. These procedures may be subdivided into local flap, distant flap and grafting. Procedures involving local flaps are usually adequate to close minor to moderate size defects. Those procedures utilizing the buccal mucoperiosteal flap as the tissue closure include straight-advancement, rotated, sliding and transversal flap procedures; while those involving the palatal mucoperiosteum are straight advancement, rotational-advancement, hinged and island flap procedures. The combinations of various local flaps to strengthen the tissue closure are also being advocated. The advantages and the limitations of these procedures are discussed. Distant flaps and bone grafts are usually indicated in the closure of larger defects in view of their greater tissue bulks. Tongue flaps have superseded extra-oral flaps from extremities and forehead for aesthetic reasons and also in view of their similar tissue replacement. Various tongue flap procedures are described. At present, various alloplastic materials such as gold, tantalum and polymethylmethacrylate are infrequently reported in the closure of oroantral fistulas. However, in the light of successful reports over the use of biological materials, collagen and fibrin, in the closure of oroantral fistulas, there seems to be another simple alternative technique for treating oroantral fistulas.